A Study on Factors Influencing Individual Taxpayers’ Compliance using The Theory of Planned Behaviour - D, Dr. Susana; P, Varshini (Journal of Contemporary Research in Management (JCRM), 2022)
During the COVID-19 pandemic, lockdown restrictions were imposed and the functioning of several business operations came to a standstill, and individuals were rendered jobless, burdened with salary cuts, or incurred loss in their business. This led to a loss in the individuals’ earnings and the Indian Government had relaxed the norms for paying taxes to overcome the crisis for the individuals. This paper was set to examine the factors that impact individual taxpayer compliance in such a challenging situation. Tax compliance refers to a taxpayer’s compliance with domestic tax regulations. The study employed the constructs of the Theory of Planned Behaviour (TPB), attitude, subjective norms, and perceived behavioural control along with the additional five constructs, tax morale, tax fairness, perception of government expenditure, tax knowledge, and tax penalty, to understand the perception of the individuals on tax compliance during the pressing times. The survey was administered among 450 respondents in Tamil Nadu using a structured questionnaire and a structural equation modelling technique was employed for analysis. The findings of this study revealed that tax morale, tax awareness, and tax penalties have a significant influence on people’s tax compliance behaviour, while tax fairness and Government spending perceptions have minimal impact. Attitudes and perceived behavioural control were found to have a substantial influence on tax compliance intention, but subjective norms (tax fairness and perception of government spending) had no significant impact. The research findings will be beneficial to policymakers to understand the key factors influencing the tax compliance of individuals.